IMPLEMENTATION OF E-PROCUREMENT IN THE PROCUREMENT OF GOODS AND SERVICES IN THE GOODS AND SERVICES PROCUREMENT WORK UNIT KARIMUN DISTRICT - Frinda Novita; Maya Nadila; Azmi (Yayasan Wayan Marwan Pulungan, 2024)
This research is motivated by the implementation of e-procurement in the procurement of goods and services at the Karimun Regency Goods and Services Procurement Work Unit, which is still not optimal and has obstacles in the implementation process. The research aims to determine the implementation of e-procurement in the procurement of goods and services, to find out the supporting factors and inhibiting factors in the process of implementing e-procurement in the procurement of goods and services at the Karimun Regency Goods and Services Procurement Work Unit. The data analysis used is qualitative with data collection techniques, namely interviews, observation, and documentation. The sampling techniques used in this research were purposive samples and snowball samples. In this study, 7 people met the sample characteristics. This research uses the theoretical basis of policy implementation by George C Edward III. The results of this research show that the implementation of e-procurement in the procurement of goods and services at the Karimun Regency Goods and Services Procurement Work Unit is generally good but not yet optimal in terms of the number of human resources, equipment resources, budget resources, and fragmentation